Effects of hyperthermia on cerebral blood flow and metabolism during prolonged exercise in humans - Nybo, L.; Møller, K.; Volianitis, St.; Nielsen, B.; Secher, N. H. (Journal of Applied Physiology, 2002)
The development of hyperthermia during prolonged exercise in humans is associated with various changes in the brain, but it is not known whether the cerebral metabolism or the global cerebral blood flow (gCBF) is affected. Eight endurance-trained subjects completed two exercise bouts on a cycle ergometer. The gCBF and cerebral metabolic rates of oxygen, glucose, and lactate were determined with the Kety-Schmidt technique after 15 min of exercise when core temperature was similar across trials, and at the end of exercise, either when subjects remained normothermic (core temperature = 37.9°C; control) or when severe hyperthermia had developed (core temperature = 39.5°C; hyperthermia). The gCBF was similar after 15 min in the two trials, and it remained stable throughout control. In contrast, during hyperthermia gCBF decreased by 18% and was therefore lower in hyperthermia compared with control at the end of exercise (43 ± 4 vs. 51 ± 4 ml · 100 g1 · min1; P < 0.05). Concomitant with the reduction in gCBF, there was a proportionally larger increase in the arteriovenous differences for oxygen and glucose, and the cerebral metabolic rate was therefore higher at the end of the hyperthermic trial compared with control. The hyperthermia-induced lowering of gCBF did not alter cerebral lactate release. The hyperthermia-induced reduction in exercise cerebral blood flow seems to relate to a concomitant 18% lowering of arterial carbon dioxide tension, whereas the higher cerebral metabolic rate of oxygen may be ascribed to a Q10 (temperature) effect and/or the level of cerebral neuronal activity associated with increased exertion.